Level of Knowledge and Causes of Dental Disease among the Students of Selected Secondary Schools in Dhaka City (Bangladesh Journal of Dental Research & Education, 2013)
To assess the level of knowledge and causes of dental disease among the urban school children a cross-sectional study was conducted in two secondary schools of Dhaka city. 20 students each of class 6, 7 & 8 from each school were randomly selected. List of the students was obtained from the teacher & from the list 20 were selected. Regarding the level of knowledge 54% were found to have average knowledge and 25.8% had good knowledge about causes of dental disease. People should be made more aware about the maintenance of oral hygiene for ensuring better oral health.DOI: http://dx.doi.org/10.3329/bjdre.v3i1.16589 Bangladesh Journal of Dental Research & Education Vol.3(1) 2013: 12-15